2018
DOI: 10.1155/2018/2957427
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Virtual Doors: A New Method to Study Gait Impairments and Freezing of Gait in Parkinson’s Disease

Abstract: Studying freezing of gait (FOG) in the lab has proven problematic. This has primarily been due to the difficulty in designing experimental setups that maintain high levels of ecological validity whilst also permitting sufficient levels of experimental control. To help overcome these challenges, we have developed a virtual reality (VR) environment with virtual doorways, a situation known to illicit FOG in real life. To examine the validity of this VR environment, an experiment was conducted, and the results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Factors that trigger and relieve FoG suggest that this is a complex entity with multiple interconnected mechanisms. FoG mostly occurs during walking through narrow passages (14), situations of cognitive overload (e.g., dual tasks) (15), anxiety (16), and turning movements (17). Factors that alleviate freezing are certain visual patterns (e.g., stripes on the floor) (18), auditory cues (19), proprioceptive and haptic stimuli (20), and other compensation strategies (21).…”
Section: Freezing Of Gait: a Puzzling Phenomenonmentioning
confidence: 99%
“…Factors that trigger and relieve FoG suggest that this is a complex entity with multiple interconnected mechanisms. FoG mostly occurs during walking through narrow passages (14), situations of cognitive overload (e.g., dual tasks) (15), anxiety (16), and turning movements (17). Factors that alleviate freezing are certain visual patterns (e.g., stripes on the floor) (18), auditory cues (19), proprioceptive and haptic stimuli (20), and other compensation strategies (21).…”
Section: Freezing Of Gait: a Puzzling Phenomenonmentioning
confidence: 99%
“…Like research a decade ago that showed how the Nintendo Wii balance board could be used to measure and train balance [ 5 ], this study shows how the Oculus Quest, a low-cost VR gaming headset can also be used to measure and train balance in older adults [ 24 ]. Previous research has shown how lab-based VR is well tolerated by more vulnerable groups, with studies showing how VR can be effectively used to cue gait in people with Parkinson’s [ 25 , 26 ], but also understand older adults’ decisions about when and how to cross a virtual road [ 27 ]. Given the power of this technology, creating VR balance games that use AI to adapt to the user’s abilities, opens a whole new vista in terms of balance rehabilitation and training possibilities [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pathological model of FoG suggests that with additional demands of sensory overload from visual or other stimuli leads to an overactivation of typical basal-ganglia pathways leading to an inhibition of movement and occurrence of freezing episodes (Lewis & Barker, 2009). Although FoG causes are multifaceted, they often occur in response of environment triggers, as turnings and passing through narrow spaces such as a doorway (Gómez-Jordana, Stafford, Peper, & Craig, 2018;Lewis & Barker, 2009;Pham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most common situations where FoG occurs involves a change in the visual environment that might require integration of visual and proprioceptive information leading to a sensory overload and a disruption in basal ganglia pathways (Cowie, Limousin, Peters, Hariz, & Day, 2012;Gómez-Jordana et al, 2018;Lewis & Barker, 2009). This disruption appears to be overcome using external sensory cues (visual, auditory and/or vibrotactile), which may help basal ganglia circuits to shifts to healthy spared neural motor pathways (Ehgoetz Martens et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation